Surgical Treatment of Superior Labral/Biceps Pathology in the Overhead Thrower. Issue 8 (15th April 2023) - Waterman, Brian R.; Dean, Robert S.; Gregory, Bonnie; Romeo, Anthony A.
Abstract : Symptomatic superior labral anterior and posterior (SLAP) tears have become an increasingly common diagnosis, particularly within the competitive overhead athlete population. Type II SLAP tears are the most encountered variant in overhead throwing athletes. Given the high incidence of false positives on advanced imaging, corroborating the history and physical examination with imaging is paramount to accurately establish a SLAP lesion diagnosis. Previous studies have reported conflicting success rates with conservative management, but the number of pitching athletes able to return to prior level of performance with nonsurgical management strategies has been unsatisfactory. Although there has historically been a notable disconnect between the incidence of SLAP tears in the literature and the number of SLAP repairs in recent investigations, high-grade or unstable tears may be candidates for débridement, labral repair, biceps tenodesis, or less frequently, biceps tenotomy. Biceps tenodesis has been increasingly used for the management of these lesions, with recent studies reporting high rates of return to sport, high satisfaction, and good to excellent patient-reported outcomes in carefully selected athletes.